God v. free will - Loh, Xi Hong (Nanyang Technological University, 2024)
This paper investigates the paradox between God’s foreknowledge and human free will. The compatibility between these two either is often only made possible when one is compromised. In this essay, I will be reconceptualising the metaphysical reality and God’s divine attribute, presenting a new model of resolving these conflicting concepts—specifically through the idea of multiverse. I will first outline the paradox then study and analyse the existing solutions—e.g. Open Theism and Compatabilism—before presenting my solution. I also consider the potential arguments against my solutions and addressed them accordingly. My solution aim to demonstrate the maximally excellent attributes of God, while maintain the fullest sense of human free will.